2014
DOI: 10.1117/12.2050322
|View full text |Cite
|
Sign up to set email alerts
|

A long-range camera based on an HD MCT array of 12μm pixels

Abstract: The development of a new thermal imaging camera, for long range surveillance applications, is described together with the enabling technology. Previous publications have described the development of large arrays of 12µm pixels using Metal Organic Vapour Phase Epitaxy (MOVPE) grown Mercury Cadmium Telluride (MCT) for wide area surveillance applications. This technology has been leveraged to produce the low cost 1280x720 pixel Medium Wave IR focal plane array at the core of the new camera. Also described is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…State of the art cameras, such as Selex ES's Horizon, provide advanced image processing features such as turbulence mitigation by employing a high performance FPGA [2]. Whilst it offers exceptional performance, the architecture comes with a considerable cost and power consumption.…”
Section: A System-on-a-chip Based Architecture For Low Powermentioning
confidence: 99%
“…State of the art cameras, such as Selex ES's Horizon, provide advanced image processing features such as turbulence mitigation by employing a high performance FPGA [2]. Whilst it offers exceptional performance, the architecture comes with a considerable cost and power consumption.…”
Section: A System-on-a-chip Based Architecture For Low Powermentioning
confidence: 99%
“…Figure 1 shows the pixel density of MOVPE grown MWIR MCT arrays which has increased over time, with the latest pixels being almost an order of magnitude more densely packed than those being produced at the beginning of the millennium. An earlier publication [8] addressed product development with 12µm pixels and indicated that work was ongoing on technology for 10µm and smaller pixel designs. This paper describes the initial results of that work, an MOVPE grown MCT 8µm pixel technology and its first implementation in SuperHawk™, a 1280x1024 pixel MWIR FPA.…”
Section: Introductionmentioning
confidence: 99%